Ustaz Sulam : sebuah potret ulama kampung - Muhaimin Sulam, 1964- (Petaling Jaya, Selangor : Strategic Information and Research Development Centre (SIRD), 2023)
Biography of an ulama from Perak, Malaysia.
Includes index.
In Malay.
Keywords: Sulam, -- Ustaz; Muslim scholars -- Malaysia -- Perak -- Biography; Ulama -- Malaysia -- Perak -- Biography; Muslim scholars